Subjective stress, coping and subjective well-being in women before and after the birth of their first child: a longitudinal case-study approach : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in Psychology at Massey University - Mason, Edward John (Massey University, 1987)
A longitudinal case-study approach was adopted to explore the changes in subjective stress, coping and subjective well-being in women before and after the birth of their first child. Subjects were 16 women due to have their first baby. It was planned to see· them at ten weeks, six weeks and two weeks before the expected date of birth of their baby, and two weeks, six weeks and ten weeks after the actual date of birth. Demographic information was collected in the first session. At each contact semi-structured interviews were conducted and subjects were asked to complete a questionnaire designed to measure subjective stress, coping, appraisals, and subjective well-being. The specific approach was descriptive, and the specific aim was to look for patterns and themes. However, while there were no well-defined hypotheses, it was expected that subjective stress would decrease before the birth, increase in the first month to six weeks after and decrease again towards the end of the study period. The use of coping strategies were expected to follow a similar pattern to that of subjective stress. Subjective well-being was expected to follow the opposite pattern to subjective stress and coping. It was felt that making specific predictions about appraisal emotions would not be productive since it was expected that emotional liability would cloud the data and general patterns would not emerge. Results showed that subjective stress generally decreased as the expected date of birth neared, except for those women who experienced a specific stressor unrelated to the pregnancy as such. It increased dramatically immediately after the birth and decreased gradually as the final contact approached. The predictions about coping and subjective well-being were also generally fulfilled. As expected there were no obvious general patterns for appraisal emotions. Empirical, theoretical, methodological and policy implications were discussed, and suggestions for future research were made.
Keywords: Stress (Psychology); Longitudinal studies; Adjustment (Psychology); Mothers; Case studies